Influence of nickel strike as adhesive layer on electrodeposited Zn-Co-Ni alloy and their performance in metal-finishing. (2021) - Kale, Vaibhav Namdev; Kumaraguru, S.; Saravanan, G.; Jalaluddeen, A. Syed; Rajkumar, P.; Subadevi, R.; Sivakumar, M.; Gnanamuthu, RM.
Abstract: In this work, a newly designed nickel strike adhesive layer with a combination of Zn-Co-Ni alloy material via direct current (DC) electrodeposition over the mild steel (MS). The quality of the deposition is optimized and evaluated from various parameters such as the concentration of electrolyte, current density, electrolyte temperature, and time, respectively. The optimized nickel strike Zn-Co-Ni alloy phases are obtained at 4 A/dm 2 current density and were subjected to XRD, field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), and EDS techniques. The impedance spectroscopy (EIS) and potentiodynamic polarization (Tafel) studies of as prepared alloys have been carried out in 0.1 M KCl and 3.5% NaCl solutions via three-electrode systems. The Tafel-corrosion studies illustrate that the rate of corrosion obtained of 0.1469 mm/year and represents very good corrosion resistance properties as well as good adhesion and structural properties with the environmental degradation issue.